Threat Upon Entry: Effect of Coworker Ostracism on Newcomers’ Proactive Behaviors During Organizational Socialization - Liu, Pan; Zhang, Yihua; Ji, Yan; Wu, Shaoxue (Frontiers in Psychology, 2021)
Extant literature has underlined the importance of newcomer proactive socialization to the organization. However, the effect of coworker ostracism on newcomers’ proactive behaviors has not been noticed. Drawing on the conservation of resources theory, we proposed a model exploring how coworker ostracism impacted newcomers’ proactive behaviors via the mediation of psychological availability. Through an empirical study with a sample of 263 newcomers and three waves of longitudinal data, we found that coworker ostracism had a negative effect on newcomers’ information seeking and guanxi developing. In addition, emotional intelligence enhanced the negative effect of coworker ostracism on newcomers’ psychological availability and the indirect influence of coworker ostracism on newcomers’ proactive behaviors via psychological availability. Important theoretical and practical implications are discussed.